2008
DOI: 10.1016/j.econedurev.2006.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency, technology and productivity change in Australian universities, 1998–2003

Abstract: In this study, productivity growth in thirty-five Australian universities is investigated using nonparametric frontier techniques over the period 1998 to 2003. The inputs included in the analysis are full-time equivalent academic and non-academic staff, non-labour expenditure and undergraduate and postgraduate student load and the outputs are undergraduate, postgraduate and PhD completions, national competitive and industry grants and publications. Using Malmquist indices, productivity growth is decomposed int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
154
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(166 citation statements)
references
References 27 publications
5
154
1
6
Order By: Relevance
“…DEA applications within the higher education sector as a typical multi-input and multioutput production environment are numerous [26][27][28][29][30][31][32][33]. In addition, the Malmquist index for analysing longitudinal developments over time [34][35][36] has also been applied for universities, e.g., for the Philippines [37] and Australia [38].…”
Section: Introductionmentioning
confidence: 99%
“…DEA applications within the higher education sector as a typical multi-input and multioutput production environment are numerous [26][27][28][29][30][31][32][33]. In addition, the Malmquist index for analysing longitudinal developments over time [34][35][36] has also been applied for universities, e.g., for the Philippines [37] and Australia [38].…”
Section: Introductionmentioning
confidence: 99%
“…Their research includes five evaluation indexes, involving 30 decisionmaking units, and the results showed that DEA is a feasible method in evaluating Universities' performance [2]. Another instance, Worthington,A.C(2008) use Malmquist Index study the varies of teaching efficiency of Australian universities between 1998 to 2003, the results show that the teaching efficiency of Australian university increased by 3.3% per year during this period on average [3]. K Chen and IS Chen (2011) using data envelopment analysis method to study the teaching performance of Taiwan colleges and universities, the results show that 73% of Taiwan's colleges and universities are in a relatively inactive state, the authors also have put forward measures to integrate innovation and reduce costs [4].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive list of DEA applications to educational organizations is available in the International Handbook on the Economics of Education ( Johnes, 2004 ) , and an examination of DEA applications to schools at all levels can be found in the Handbook of Data Envelopment Analysis ( Cooper et al , 2004 ). A few examples of its use to evaluate institutions of higher education include ( Beasley, 1990( Beasley, , 1995( Beasley, , 2003Breu and Raab, 1994 ;Athanassopoulos and Shale, 1997 ;Avkiran, 2001 ;Korhonen et al , 2001 ;Abbott and Doucouliagos, ജ 2003 ;Casu and Thanassoulis, 2006 ;Glass et al , 2006 ;Worthington and Lee, 2008 ) .…”
Section: > 0 For Allmentioning
confidence: 99%